2006
DOI: 10.1038/nature05313
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Dll4 signalling inhibits tumour growth by deregulating angiogenesis

Abstract: Haploinsufficiency of Dll4, a vascular-specific Notch ligand, has shown that it is essential for embryonic vascular development and arteriogenesis. Mechanistically, it is unclear how the Dll4-mediated Notch pathway contributes to complex vascular processes that demand meticulous coordination of multiple signalling pathways. Here we show that Dll4-mediated Notch signalling has a unique role in regulating endothelial cell proliferation and differentiation. Neutralizing Dll4 with a Dll4-selective antibody rendere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

53
873
6
8

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 892 publications
(950 citation statements)
references
References 20 publications
53
873
6
8
Order By: Relevance
“…We have previously shown that Notch activation in melanoma has a critical role in driving tumor progression (Balint et al, 2005;Liu et al, 2006), and defined an oncogenic role for Notch signaling in melanocytic transformation (Pinnix et al, 2009). Additionally, Notch and Notch ligands, for example, Delta-like 4 (Dll4), are robustly expressed in tumor endothelial cells in comparison with that in neighboring, normal tissue vessels (Mailhos et al, 2001), and vascular endothelial growth factor, which can be predominately produced by tumor cells, can induce endothelial cells to express Notch1 and Dll4 (Liu et al, 2003;Noguera-Troise et al, 2006;Ridgway et al, 2006). In fact, blockade of Dll4-Notch signaling is an emerging therapeutic approach to inhibit tumor angiogenesis (Thurston et al, 2007;Dufraine et al, 2008;Yin et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that Notch activation in melanoma has a critical role in driving tumor progression (Balint et al, 2005;Liu et al, 2006), and defined an oncogenic role for Notch signaling in melanocytic transformation (Pinnix et al, 2009). Additionally, Notch and Notch ligands, for example, Delta-like 4 (Dll4), are robustly expressed in tumor endothelial cells in comparison with that in neighboring, normal tissue vessels (Mailhos et al, 2001), and vascular endothelial growth factor, which can be predominately produced by tumor cells, can induce endothelial cells to express Notch1 and Dll4 (Liu et al, 2003;Noguera-Troise et al, 2006;Ridgway et al, 2006). In fact, blockade of Dll4-Notch signaling is an emerging therapeutic approach to inhibit tumor angiogenesis (Thurston et al, 2007;Dufraine et al, 2008;Yin et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…[69][70][71], inhibiting a signaling pathway predominantly activated in the CSCs (e.g., Notch, Wnt etc.) [72,73], immunomodulation (e.g., CD326, ALDH1 inhibitor) [73,74], sensitizing CSCs to systemic chemotherapy/radiation (e.g., IL4, hyaluronate receptor) [56,75] or inhibiting CSC angiogenesis (e.g., VEGF-R, DLL4) [76][77][78]. An important contribution of CSC research to anti-cancer targeted treatment is that it unveils specific biomarkers which can be targeted in vivo by antibody therapy leading to disrupted tumor growth [60,67,79,80].…”
Section: Targeted Therapy-targeting Cscs In Wtmentioning
confidence: 99%
“…The delta-like ligand (Dll) 4, expressed in endothelial cells, is critical for vascular development (Benedito and Duarte, 2005). Using the neutralizing antibodies of Dll4 in glioma leads to an increase of the dysfunctional vascular system (NogueraTroise et al, 2006;Ridgway et al, 2006), resulting in poor tumor perfusion, poor oxygenation, and reduced tumor growth. Due to the essential role of Notch signaling in glioma progression, gamma-secretase inhibitors (GSI), which block Notch activation by transcriptional regulation, can be considered as good candidates for glioma therapeutic drugs (Miele et al, 2006;Gordon et al, 2008;Kovall, 2008).…”
Section: Notch Signaling Pathways and Potential Therapeutic Approachesmentioning
confidence: 99%